Display of GPI‐anchored anti‐EGFR nanobodies on extracellular vesicles promotes tumour cell targeting. Issue 1 (14th March 2016) - Kooijmans, Sander A. A.; Aleza, Clara Gómez; Roffler, Steve R.; van Solinge, Wouter W.; Vader, Pieter; Schiffelers, Raymond M.
Abstract : Background: Extracellular vesicles (EVs) are attractive candidate drug delivery systems due to their ability to functionally transport biological cargo to recipient cells. However, the apparent lack of target cell specificity of exogenously administered EVs limits their therapeutic applicability. In this study, we propose a novel method to equip EVs with targeting properties, in order to improve their interaction with tumour cells. Methods: EV producing cells were transfected with vectors encoding for anti‐epidermal growth factor receptor (EGFR) nanobodies, which served as targeting ligands for tumour cells, fused to glycosylphosphatidylinositol (GPI) anchor signal peptides derived from decay‐accelerating factor (DAF). EVs were isolated using ultrafiltration/size‐exclusion liquid chromatography and characterized using western blotting, Nanoparticle Tracking Analysis, and electron microscopy. EV–tumour cell interactions were analyzed under static conditions using flow cytometry and under flow conditions using a live‐cell fluorescence microscopy‐coupled perfusion system. Results: V analysis showed that GPI‐linked nanobodies were successfully displayed on EV surfaces and were highly enriched in EVs compared with parent cells. Display of GPI‐linked nanobodies on EVs did not alter general EV characteristics (i.e. morphology, size distribution and protein marker expression), but greatly improved EV binding to tumour cells dependent on EGFR density under static conditions. Moreover, nanobody‐displaying EVs showed a significantly improved cell association to EGFR‐expressing tumour cells under flow conditions. Conclusions: We show that nanobodies can be anchored on the surface of EVs via GPI, which alters their cell targeting behaviour. Furthermore, this study highlights GPI‐anchoring as a new tool in the EV toolbox, which may be applied for EV display of a variety of proteins, such as antibodies, reporter proteins and signaling molecules.